Analisis Pemberitaan Kriminal Terhadap Wanita dan Remaja: Analisis Wacana Kritis Theo Van Leeuwen - Johar Amir (Seminar Nasional LP2M UNM, 2022)
Abstract. Human interaction is intended to be able to communicate with other people using various ways, both spoken and written. Criminal cases against women and adolescents are very interesting to analyze. Writing news about women and youth must use special treatment because if news writing is done openly it will have a negative impact, especially for underage youth. Given that the role of the media is very important in shaping the mindset of the community in responding to information that occurs around the community. Based on the background of the problems that have been described, researchers will reveal and identify carefully to obtain accurate information through a study entitled "Analysis of Reporting on Crime Against Women and Adolescents: Critical Discourse Analysis of Theo van Leeuwen". The data source used is a newspaper published by Berita Harian Kota Makassar. The techniques used in collecting data in this study were documentation techniques, reading techniques, and note-taking techniques in order to obtain data in the form of words, phrases, or sentences that characterize exclusion and inclusion in accordance with the critical discourse analysis approach according to Theo van. Based on the results of the study, (1) the exclusion strategy in Berita Harian Kota Makassar found only two strategies, namely passivation and nominalization. Berita Harian Kota Makassar is indicated to have attempted to hide actors by using a passivation strategy. (2) Makassar City Daily News was found to use nine strategies consisting of indifference, abstraction, objectivation, nomination, categorization, identification, determination, indetermination, assimilation, and individuation with a total of 127 data. (3) The strategies that were not found were differentiation, categorization, association and disassociation. It is indicated that Berita Harian Kota Makassar has tried to hide the identity of the victims or perpetrators of violence who are women and youth, this has an impact on readers who will find it difficult to identify the actors involved in an incident of violence involving women or youth.  Keywords: Analysis of Criminal Reporting, Critical Discourse Analysis of Theo van Leeuwen